Living on the Edge: Emotional and Behavioral Problems in a Sample of Kosovar Veterans and Wives of Veterans 16 Years Postwar - Shahini, Mimoza; Rescorla, Leslie A.; Shala, Merita; Ukshini, Shqipe (Frontiers in Psychiatry, 2019)
Aim:This study aimed to explore the effects of war traumatic exposure on emotional and behavioral problems in a sample of Kosovar war veterans and the wives of veterans 16 years after the 1998-99 war, as well if level of education, income, wellbeing and traumatic exposure are predictors for emotional and behavioral problems. Methods:Self-report data were obtained from 373 adults, 247 male war veterans (66.2% of the sample) and 126 wives of other male war veterans (33.8% of the sample). The sample was recruited from a list of war veterans provided by the Kosovar National Association of War Veterans. The mean age was 45.42; (SD=7.64). Measurements comprised a socio-demographic interview, the Well-Being Index (WHO-5), the HTQ, and the Adult Self Report. Logistic regression analysis was conducted to explore if the demographic variables are predictors for ASR broad scales and subscales. MANCOVA analysis was performed by adding as covariates the continuous variables pointed out in the logistic regression analysis as discriminating factors between the groups. Post-hoc analyzes were corrected and we estimated partial Eta-square to measure the effect size. Results:The higher traumatic exposure during the war, the greater the tendency to have emotional problems and behavioral problems for both participants. There were no differences on the prevalence of emotional and behavioral problems between two groups and there were no differences on seeking professional help. Wives of veterans living in rural area have shown higher scores of ASR compare to those living in urban area or even with those from veterans from urban and rural. Veterans with elementary education and poor wellbeing had the highest scores compare to other groups. Using ASR broad scales as outcome variables and Trauma exposure, smoking, drinking alcohol and wellbeing as predictors, we found that the model was significant predictor for both male and female participants. Conclusion:The relationship between the level of exposure to traumatic events and emotional and behavior problems and factors that moderate such relation, in war veterans and their wives, should help global mental health researchers address the contextual dimensions of this relationship and identifying better ways to prevent and treat those problems